PERAN INTERNAL AUDITOR DALAM MENCEGAH DAN MENDETEKSI KECURANGAN PADA ORGANISASI - Kurniawan, Widiar; Intan Marzita Saidon; Taudlikhul Afkar (Majalah Ekonomi, 2026)
Fraud is a serious problem that can threaten the sustainability of organizations in both the public and private sectors. One control mechanism that plays an important role in preventing and detecting fraud is the internal audit function. This study aims to analyze the role of internal auditors in preventing and detecting fraud in organizations. The research method used is a qualitative approach with a literature study method that examines various scientific sources related to internal auditing, internal control, and fraud. The results show that internal auditors have a strategic role in identifying fraud risks, evaluating the effectiveness of internal control systems, and providing recommendations for improvement to management. In addition, internal auditors contribute to strengthening anti-fraud awareness through improved governance and internal control practices. Therefore, the existence of an independent and professional internal audit function is essential to minimize the risk of fraud in organizations.